Respuesta :
[tex]0.00048\div(6\times10^{-4})=(48\cdot10^{-5})\div(6\cdot10^{-4})\\\\=(48:6)\cdot(10^{-5}:10^{-4})=8\cdot10^{-5-(-4)}=\boxed{8\cdot10^{-1}}\\\\Used:\\\\a^n:a^m=a^{n-m}[/tex]
The simplified expression of 0.00048 ÷ (6 × 10^-4) is Option(B) [tex]8 * 10^{-1}[/tex]
Property of exponent -
- [tex]a^{m}.a^{n} = a^{m + n}[/tex]
- [tex]\frac{a^{m} }{a^{n} } = a^{m-n}[/tex]
How to simplify the given expression ?
Given expression is - 0.00048 ÷ (6 × 10^-4)
We have = [tex](48 * 10^{-5}) / (6 * 10^{-4} )[/tex]
= [tex]\frac{48 * 10^{-5} }{6 * 10^{-4} }[/tex]
= [tex]8 * 10^{-1}[/tex] [Using the above mentioned properties]
Therefore the simplified expression is Option(B) [tex]8 * 10^{-1}[/tex] .
To learn more about simplifying expression, refer -
https://brainly.com/question/1280754
#SPJ2